PERLINDUNGAN KONSUMEN BAGI PASIEN PENGGUNA KARTU BPJS DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Irfan Ridha (Universitas Muhammadiyah Sumatera Utara, 2016)
BPJS a poverty reduction which aims to have access and quality of health care of the poor can be improved so that no poor people who have difficulty accesin health care service by reason of lack of funds. Formation BPJS in Law No. 24 on BPJS. The research problem is whether the patient card users BPJS at Arifin Achmad Hospital Riau Province to obtain protection of consumers and how to shape consumer protection against card users BPJS patients at Arifin Achmad Riau province by Law No. 8 of 1999 on consumer protection in 2015. This study examines the empirical juridical legal aspects nmelihat implementation in the field. This research was conducted by Observational Research, is to survey. Data collectors in the form of questionnaires and interviews, while the nature of the research is descriptive of providing an overview of the issues examined. Respondents were patients BPJS card users and the hospitals Pekanbaru. The conclusion of this study is to unsatisfactory services provided by the City Hospital Pekanbaru to patients BPJS card users due to lack of patient understanding about their rights and obligations. So they were not able to do anything in case of misuse of their rights. Majanemen Hospital who are not professional is also an inhibiting factor in the provision of services that are good for society.